Economic-Sociological Alternative of Karl Polanyi - Вадим Валерьевич Радаев (Journal of Economic Sociology, 2010)
Today the papers by Karl Polanyi get more and more acknowledgment including that fact that he criticized radically the formal economic theory and economic liberalism. What is the reason for this paid attention and what does the author suggest us? This paper discusses some methodological basic ideas of Karl Polanyi and focuses on those analytical possibilities that were disclosed by these ideas for different research areas. The author begins the review from the substantive definition of the “economic” and analyzes the possibilities to use it on the example of the term “home labour”. This in turn leads us to the broader topic of problems of economic survival and moral economy. Further on the next part of the paper is devoted to the most interesting topic in Polanyi’s work - to the reciprocity form of the economic integration. The paper ends by transferring to the macro level discussion about capitalism and self-regulated markets, the key topic of the book “The great transformation”.